The relationship between workload, social support, work motivation, and emotional stress among working mothers in Malaysian public hospitals - Azmi, Emilia Nurfarah Ain; Ma’rof, Aini Azeqa; H. Hamsan, Hanina (Human Resource Management Academic Research Society, 2024)
This study explores the relationship between workload, social support, work motivation, and emotional stress among working mothers in Malaysian public hospitals. The research examines how key dimensions—workload, perceived social support, and work motivation— impact emotional stress levels. A sample of 453 working mothers was analyzed using quantitative methods, including correlation and regression analyses. The results reveal that workload is the strongest predictor of emotional stress, followed by social support and work motivation. Higher workload was significantly associated with increased emotional stress, while greater social support and higher motivation contributed to lower stress levels. These findings highlight the critical need for effective workload management, robust support systems, and motivational strategies in healthcare settings to reduce emotional stress and enhance well-being among working mothers. The study offers valuable insights into the interplay of these factors and provides practical recommendations for improving employee well-being in public hospitals.